OPTIMIZING THE UTILIZATION OF NILE TILAPIA (OREOCHROMIS NILOTICUS LINN.) AS GROWTH AND SURVIVAL RATE BIOCATALYST PRAWNS (MACROBRACHIUM ROSENBERGII DE MAN) - Rachmawati, Armeina Nur; Sunarto, Sunarto; Raharjo, Agung Budi (Prodi Pendidikan Biologi FKIP UNS, 2012)
ABSTRAK Prawns (Macrobrachium rosenbergii de Man) is one of fishery commodities of high economic value. Maintenance monoculture can cause ecosystem balance problems because almost all shrimp collected in the bottom of the pool so that the biological processes that take place in the pool water is not controlled. This situation can encourage the onset of blooming of plankton that causes a decrease in dissolved oxygen content so that the prawns experience stress and can inhibit the growth of giant prawns and decreased production. This study aims to examine the use of Nile Tilapia as growth and survival rate biocatalyst of prawns. The research was conducted from February to June 2011 in the village of Jimus, Karanglo, Klaten and Sub Lab Biology, Laboratory of Mathematics and Science Center UNS. This research used Completely Randomized Design polyculture system 2 treatment and control with 20 head of stocking juvenile shrimp (PL 21) per m2 on the pool measures 8 x 2 x 1 m3. After 21 days of stocking juvenile shrimp followed by stocking nile tilapia. Parameters measured include growth (weight and length) prawns, survival rate, and water quality of the cultivation. The results showed that survival rates of prawns are high achieved with maintenance treatment with dense stocking tilapia 5 nile tilapia ie 85.11%. The range of water quality during the study between temperature 25-310C, dissolved oxygen content from 4,06 to 9,78 mg / L, the degree of acidity of water from 6.40 to 8.10, 0 ppt salinity, ammonia (NH3) from 0.003 to 0.014 mg / L, nitrite (N02) from 0.003 to 0.201 mg / L, nitrate (N03) from 0.307 to 4.05 mg / L, phosphate (P04) from 0.364 to 1.09 mg / L. Thus, maintenance treatment of tilapia provide a good influence on the stability of the prawns media resulting in the maintenance of survival (survival rate) is quite good. Kata kunci: Macrobrachium rosenbergii de Man, biocatalyst, Oreochromis niloticus Linn.